The Generation of Turnip Crinkle Virus-Like Particles in Plants by the Transient Expression of Wild-Type and Modified Forms of Its Coat Protein - Saunders, Keith; Lomonossoff, George P. (Frontiers in Plant Science, 2015)
Turnip crinkle virus (TCV), a member of the genus carmovirus of the Tombusviridae family, has a genome consisting of a single positive-sense RNA molecule that is encapsidated in an icosahedral particle composed of 180 copies of a single type of coat protein. We have employed the CPMV-HT transient expression system to investigate the formation of TCV-like particles following the expression of the wild-type coat protein or modified forms of it that contain either deletions and/or additions. Transient expression of the coat protein in plants results in the formation of capsid structures that morphologically resemble TCV virions (T = 3 structure) but encapsidate heterogeneous cellular RNAs, rather than the specific TCV coat protein messenger RNA. Expression of an amino-terminal deleted form of the coat protein resulted in the formation of smaller T = 1 structures that are free of RNA. The possibility of utilizing TCV as a carrier for the presentation of foreign proteins on the particle surface was also explored by fusing the sequence of GFP to the C-terminus of the coat protein. The expression of coat protein-GFP hybrids permitted the formation of VLPs but the yield of particles is diminished compared to the yield obtained with unmodified coat protein. Our results confirm the importance of the N-terminus of the coat protein for the encapsidation of RNA and show that the coat protein's exterior P domain plays a key role in particle formation.